Audit Sistem Informasi Menggunakan Framework COBIT5 Pada Sistem informasi Akademik Universitas Alma Ata - Rachmat Darmawan; Tri Rochmadi; Dadang Heksaputra; Yanuar Wicaksono (Informatik : Jurnal Ilmu Komputer, 2025)
The rapid development of information technology encourages universities to provide fast, effective, and integrated academic services. Alma Ata University has implemented an Academic Information System (SIAKAD) which functions as a service support in the learning process. However, this system is still faced with several obstacles, including constrained access speed when filling in attendance and the occurrence of recurring service interruptions. This research aims to evaluate the capability level of SIAKAD and develop recommendations for improvement based on the results of the audit conducted with the COBIT 5 framework, especially in the Deliver, Service, and Support (DSS) domain. The methodology applied is mixed methods, which combines qualitative and quantitative approaches. The research findings show that the capability of each subdomain is measured at level 4 (Predictable Process), while the desired target is level 5 in each DSS subdomain. Thus, it can be concluded that SIAKAD of Alma Ata University has been operating well and consistently, but requires improvement steps to achieve the expected level 5.